HUMAN RIGHTS, FUNDAMENTAL FREEDOMS AND UNIVERSAL VALUES IN INTERNATIONAL RELATIONS - L. S. Voronkov (Vestnik MGIMO-Universiteta, 2016)
The author analyzes the evolution of human rights and fundamental freedoms in domestic political life of individual states and in international relations as well over the latest two centuries. The article traces the role of struggle for liberal political human rights and civilian freedoms in the dismantling of the feudal-absolutist regimes as well as the challenges of radical left-wing (communist) and far right-wing (national-socialistic) threats to be met by the supporters of liberal political rights and civil freedoms in the interwar period. The list of human rights and fundamental freedoms had constantly been updating in the postwar period, including by the efforts of the UNO and other international organizations, and fixing in different international documents. The author emphasizes the import role of the Conference on Security and Cooperation in Europe (CSCE) in transforming the issues of human rights and fundamental freedoms into the essential element of public diplomacy of contemporary states. He traces the process of the increasing utilization of liberal political rights and civilian freedoms, which are usually the effective tools for domestic democratic transformation, within the framework of diplomatic practice of European and North-American states, aimed at ensuring their political and economic interests on the world stage. In this regard the author addresses the attempts of Western countries to legalize "humanitarian"interventions in circumvention of the UN Security Council. The article emphasizes the necessity to replenish the understanding of universal human rights and freedoms by the values, developed both by the international community within the framework of implementing the Millennium Development Goals and by various countries and peoples, which in sum constitute the modern international civilizational baggage.